LATERALITY AND RHYTM BY GENDER, IN PRE-ADOLESCENT STUDENTS (Fiep Bulletin - online, 2011)
The objective the study has been verifying whether there were lower limbs and bilateral pace asymmetries or not, in 10-11-year-old pre-adolescents, students at municipal schools, in Dourados-MS. It were used the tests for speed and agility and the Test of Time (ability to repeat a rhythm in dislocation), both of Johnson & Nelson, in Marins and Giannichi (1998). The motor exploration is the development of a positive self-concept in each child. In this case, it was also checked out if there were deviations on the number of heartbeats, for each speed. The rhythmic experience, lived with their own paces, adjusts to the data from the space and must be kept through the time-perception work and, particularly, through the game play of internalizing their own motion rhythms. The rhythm in motor development is an important tool for the association and understanding of the rhythm, structural support for thoughtfulness in education, since it commands the basic locomotion forms of the man throughout its existence (VERDERI, 2000). The hypothesis to be verified regards the fact boys are more active than girls, given that they are more involved with game ball since they toddle, therefore, they will have better motor performance, carrying the body with greater control in space. After the statistical treatment of the tests applied, the test t of Student indicated that the test runtimes are not equal between the genders, pointing that the average test running time has differed significantly (t(114) = 2,146; p = 0,033) between male and female adolescents, it is significant for male students and confirms the hypothesis stated, as well the gap in the School Physical Education. Concerning the evaluation of the three rhythmic speeds, in the average, in the three tests, it was verified that 130 (87.2%) out of the adolescents performed the test markedly or totally out of the rhythm, and within these ones 50 (38.5%) are from masculine gender and 80 (61.5%) from feminine. The difference is statistically significant (²(1)= 4,161; p = 0,041), whereas the girls had greater difficulty in running with the three tests of walking in the rhythm, only 19 (12.8% ) have accomplished it in the rhythm or moderately off. The results show that is necessary to prioritize the development of the rhythmic scheme even before teaching motion games, as recommended by Le Boulch.
Keywords: Laterality; Pace; Pre-adolescents